1970
DOI: 10.1063/1.1659285
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Isoperibol Calorimetry for Laser Power and Energy Measurements

Abstract: Laser power and energy measurements are commonly made in calorimeters operating in a constant temperature environment. Calorimeters of this type are analyzed in terms of the first law of thermodynamics and the boundary value problem describing heat flow in the calorimeter. This theory of the measurement suggests design features of the calorimeter, sources of error to be avoided in design and operation, and tests to demonstrate experimentally the adequacy of the design. The analysis shows how time—temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 10 publications
4
53
0
Order By: Relevance
“…Volume absorbing transfer standards have also been calibrated and characterized for measuring pulsed laser radiation at a wavelength of 10.6 pm using a transversely excited, atmospheric pressure (TEA) CO2 laser source. 1 This NBS TEA laser is used in single mode configuration to measure pulse energy and detector responsivity as summarized in Table 4. …”
Section: Measurement Capabilitiesmentioning
confidence: 99%
“…Volume absorbing transfer standards have also been calibrated and characterized for measuring pulsed laser radiation at a wavelength of 10.6 pm using a transversely excited, atmospheric pressure (TEA) CO2 laser source. 1 This NBS TEA laser is used in single mode configuration to measure pulse energy and detector responsivity as summarized in Table 4. …”
Section: Measurement Capabilitiesmentioning
confidence: 99%
“…In all these applications, the air flow through the calorimeter during measurement has been fixed at an arbitrarily selected rate, in most cases, at a fairly high flow rate to insure quick calorimetric response and consistent burning of the material. The theory of isoperibol calorimeter [1,2] implies that varying air flow would affect the rate of calorimetric response, but not the total work (heat input) done on the calorimeter. However, this has not been substantiated experimentally.…”
Section: Introduction the Isoperibol Calorimetric Technique Has Been mentioning
confidence: 99%
“…in considerable detail and applied extensively in thermochemistry [1][2][3]. Its subsequent applications in the area of polymer and textile combustion has demonstrated that the technique is a unique and effective tool in the evaluation of material flammability [4,5] and efficiency of flame retardants [6][7][8][9], and on the study of the mechanism of flame retardant action [10][11][12].…”
Section: Introduction the Isoperibol Calorimetric Technique Has Been mentioning
confidence: 99%
“…1 J/ crrr' for shorter pulses). The C-series calorimeters and the theory of isoperibol calorimetry have been described elsewhere [4], [6]. The Center for Devices and Radiological Health (CDRH) of the Food and Drug Administration (FDA) also maintains a C-series calorimeter.…”
Section: Introductionmentioning
confidence: 99%